Cutaneous mucormycosis: Unveiling rare manifestations - Jyoti Jindal; Vikas Garg (Journal of Family Medicine and Primary Care, 2025)
Mucormycosis is a rare but life-threatening fungal infection caused by Mucorales, with high morbidity and mortality rates, especially among immunocompromised individuals. We report six cases of rare manifestations of cutaneous mucormycosis. To describe rare manifestations of cutaneous mucormycosis, highlighting the importance of prompt recognition and treatment to improve patient outcomes. Retrospective review of medical records from 2021 to 2023. This case series presents six patients with rare manifestations of cutaneous mucormycosis. The patients’ ages ranged from 25 to 60 years, with an equal male-to-female ratio. Comorbidities included diabetes, HIV/AIDS, chronic kidney disease, connective tissue disorder, leukemia, and systemic lupus erythematosus (SLE). All six patients (100%) presented with cutaneous mucormycosis, with varying clinical manifestations, including necrotizing fasciitis of the scalp (16.7%), cutaneous lesions of the buttock (16.7%), fungal keratitis and endophthalmitis with periorbital cutaneous lesions (16.7%), mucormycotic abdominal wall lesions (16.7%), mucormycotic osteomyelitis of the mandible with overlying skin blackening (16.7%), and cerebral vasculitis with scalp skin lesions (16.7%). The most common clinical features are fever (83.3%), pain (66.7%), and swelling (50%). Laboratory findings include elevated WBC count (83.3%), positive fungal culture (100%), and histopathology (83.3%). Treatment consisted of surgical debridement (83.3%), antifungal therapy with amphotericin B (100%), and supportive care. Outcomes were favorable, with one patient achieving complete recovery (16.7%), four showing improvement (66.7%), and one experiencing disease stabilization (16.7%). Notably, no mortality was reported. Cutaneous mucormycosis can manifest in diverse ways. Early recognition and treatment are crucial to prevent morbidity and mortality associated with this rare and devastating fungal infection.